ANALISIS PENGARUH SBI, INDEKS OBLIGASI PEMERINTAH, NILAI KURS, HARGA CPO DAN INFLASI TERHADAP KONTRAK FUTURES KOMODITI OLEIN DI BURSA BERJANGKA JAKARTA PERIODE 2011-2013 - Pramasha, Alvin Rayinda; Widyarti, Endang Tri (Faculty of Economics and Business Diponegoro University, 2015)
Futures exchange is a place or container that is used to do the transaction buy / sell futures in the form of commodities and precious metals to make an investment. One of the investments contained in the Jakarta Futures Exchange is a commodity futures contract olein. Futures contract is an agreement to buy or sell an asset at a certain period of time in the future with certainty the price agreed in advance. Investors will consider investing in two things: the price of the futures contract and the risk of a futures contract itself. investors are rational thinking will always obtain investment and perform various analyzes to reduce uncertainty in the investment or reduce risk. This study aims to analyze the factors affecting particular commodity futures contract olein listed on the Jakarta Futures Exchange during 2011-2013. The variables studied were the interest rate of SBI, Government Bond Index, Value Exchange, CPO prices, and inflation. This study was performed using multiple linear regression analysis, the data collection tool used was an observational study and literature study with time series data and the data used in the commodity futures contract futures contract futures olein is a 1 month no research. The results of the regression analysis show that is Value Exchange, crude palm oil price and a significant positive effect on commodity futures contracts olein. SBI interest rates, and inflation are significantly and negatively related to commodity futures contracts olein. While the Government Bond index variable and not significant positive effect on commodity futures contracts olein.